Analisis Model Beneish Dalam Mendeteksi Kecurangan Laporan Keuangan Pada BUMN Karya - Santy Aji Sitohang Sitohang; Yanuke Patricia Siahaan; Ramly Siahaan; Roris Tua Pandiangan (IJMA (Indonesian Journal of Management and Accounting), 2026)
ABSTRACT This research aims to detect indications of fraud in the financial reports of state-owned construction companies for the 2021-2025 period. The purpose of this study is to determine the most dominant indicators for detecting fraud. The fraud detection tool selected is the Beneish model. The data required for this study is secondary data in the form of financial reports obtained from the official IDX website. The research data was analyzed using quantitative descriptive methods. The results of the M-Score analysis identified three manipulator companies and one non-manipulator company for the 2021-2025 period. The companies detected as manipulators were WSKT in 2022, WIKA in 2021-2022, and ADHI in 2023. Meanwhile, PTPP was categorized as a non-manipulator from 2021-2025. The most potential indicators for fraud include a high increase in accounts receivable (DSRI), drastic sales growth (SGI), and an increase in accrual value (TATA). This M-Score calculation analysis is only capable of identifying red flags, necessitating a forensic audit to provide definitive evidence of fraud. The results of this research are expected to positively impact report users, such as helping investors avoid investing in companies that manipulate financial statements and assisting auditors in focusing their audits on areas with a high risk of fraudulent practices.   ABSTRAK Penulisan riset ini bertujuan untuk mendeteksi apakah terdapat indikasi kecurangan dalam laporan keuangan perusahaan BUMN Karya pada periode 2021-2025. Untuk mengetahui indikator yang paling dominan mendeteksi indikasi kecurangan. Alat deteksi kecurangan yang dipilih adalah model Beneish. Data yang dibutuhkan dalam penulisan kajian ini adalah data sekunder berupa laporan keuangan yang diperoleh dari situs resmi BEI. Data penelitian dianalisis dengan metode deskriptif kuantitatif. Hasil analisis M-Score mengidentifikasikan tiga perusahaan manipulator dan satu perusahaan non manipulator dalam kurun waktu 2021-2025. Perusahaan yang terdeteksi sebagai manipulator adalah WSKT tahun 2022, WIKA tahun 2021-2022 dan ADHI tahun 2023. Sementara PTPP masuk kategori non manipulator dari tahun 2021-2025. Indikator yang paling potensial dalam indikasi kecurangan mencakup peningkatan piutang usaha yang tinggi (DSRI), pertumbuhan penjualan yang drastis (SGI) dan peningkatan nilai akrual (TATA). Analisis perhitungan M-Score ini hanya mampu mengidentifikasi tanda bahaya (red flags) sehingga perlu melakukan audit forensik untuk menghasilkan bukti final terjadinya kecurangan. Hasil riset ini diharapkan memberikan kontribusi positif bagi pengguna laporan seperti membantu investor menghindari investasi pada perusahaan manipulator serta membantu auditor untuk lebih fokus melakukan pemeriksaan terhadap rasio yang memiliki risiko tinggi diterapkan dalam tindakan manipulasi.